A fresh look at the photoelectron spectrum of bromobenzene: a third-order non-Dyson electron propagator study - Schneider, Matthias; Wormit, Michael; Dreuw, Andreas (The journal of chemical physics, 2015)
The valence-shell ionization spectrum of bromobenzene, as a representative halogen substituted aromatic, was studied using the non-Dyson third-order algebraic-diagrammatic construction [nD-ADC(3)] approximation for the electron propagator. This method, also referred to as IP-ADC(3), was implemented as a part of the Q-Chem program and enables large-scale calculations of the ionization spectra, where the computational effort scales as n5 with respect to the number of molecular orbitals n.
Gesehen am 11.12.2017